Sensitivity of individual‐donation and minipool nucleic acid amplification test options in detecting window period and occult hepatitis B virus infections. Issue 10 (17th October 2013) - Vermeulen, Marion; Coleman, Charl; Mitchel, Josephine; Reddy, Ravi; van Drimmelen, Harry; Ficket, Tracy; Lelie, Nico
Abstract : Background: Several comparison studies showed that the Ultrio assay (Novartis Diagnostics) used in individual‐donation nucleic acid amplification testing (ID‐NAT) format was as sensitive as the TaqScreen assay (Roche) on minipools of six donations (MP6), but the sensitivity of HBV DNA detection has been improved in the new Ultrio Plus version of the assay. A head‐to‐head comparison study was designed to compare the clinical sensitivity of the Ultrio and Ultrio Plus assay in ID, MP4, and MP8 formats using TaqScreen MP6 as a reference assay. Study Design and Methods: Plasma samples of 107 hepatitis B surface antigen (HBsAg)‐negative, HBV ID‐NAT (Ultrio) positive‐yield samples and 29 HBV DNA–negative, HBsAg‐positive samples were used for comparison of NAT options in replicate testing of dilutions. Viral loads and relative sensitivities were determined by probit analysis against the Eurohep standard. Results: Ultrio Plus detected a significantly (p < 0.00001) higher proportion of replicate assays on HBV NAT yields (77%) than Ultrio ID (62%) and TaqScreen MP6 (47%), whereas Ultrio Plus MP4 and MP8 detected 53 and 41%, respectively. On HBsAg‐yield samples missed by Ultrio screening, the reactivity rate increased significantly (p < 0.0001) from 23% in Ultrio to 65% in Ultrio Plus and further to 72% (p = 0.10) in the TaqScreen assay. The overall improvement factor of the analytical sensitivity offered by the target enhancer reagent in the Ultrio Plus assay was 2.5 (2.0‐3.1)‐fold on the Ultrio yield samples, but 43 (11‐350)‐fold on the HBsAg yields. In ID‐NAT format the analytical sensitivity of TaqScreen relative to Ultrio Plus was 2.0 (1.0‐4.2), 0.9 (0.7‐1.3), and 1.6 (0.9‐3.0) on the Eurohep standard, HBV NAT–, and HBsAg‐yield samples respectively. Conclusion: The clinical sensitivity of the currently available commercial NAT methods is mainly driven by the pool size.